Impact Of Training On The Adoption Of Backyard Poultry Rearing Practices In Ambala District Of Haryana - Dular, R. K.; Singh , Upasana; Kumar , Ramesh (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was carried out in Ambala district of Haryana to evaluate the impact of training programmes on adoption of improved backyard poultry rearing practices. The practice wise adoption index showed that feeding and watering (72.75%) was highly adopted followed by housing and management (61.84%) and breeds and breeding (44.21%). The least adoption was for health care practices (41.58%). The overall adoption index was 54.87%. The findings of the correlation analysis revealed that extent of adoption of improved backyard poultry rearing practices had positive and significant relationship with education, occupation, flock size, annual income, availability of improved birds, mass media exposure, extension contact, economic motivation and attitude. While in case of age, caste and land holding, it was non-significant. It can be inferred from the study that extension agencies should be geared up and should continue their efforts in accelerating the rate of adoption of different backyard poultry rearing practices.